TG6002 oncolytic vaccinia virus and chemotherapy synergy: a promising strategy for pancreatic ductal adenocarcinoma - Foloppe, Johann; Farine, Isabelle; Pichon, Christelle; Kempf, Juliette; Hortelano, Julie; Moreau, Baptiste; Cochin, Sandrine; Takeda, Armelle; Pessaux, Patrick; Erbs, Philippe (Frontiers in Microbiology, 2025)
Pancreatic ductal adenocarcinoma (PDAC) is a highly malignant cancer characterized by poor prognosis and limited treatment options, often associated with significant toxicity. Recently, we described TG6002, an oncolytic vaccinia virus (VACV) engineered for tumor-selective replication through the deletion of thymidine kinase and ribonucleotide reductase genes. TG6002 also expresses the suicide gene FCU1, which efficiently converts the non-cytotoxic prodrug 5-fluorocytosine (5-FC) into the chemotherapeutic agent 5-fluorouracil (5-FU). In this study, we evaluated the efficacy of TG6002, both alone and in combination with 5-FC, in human PDAC cell lines, xenograft and orthotopic PDAC models, as well as ex vivo in live patient-derived pancreatic cancer tissues. Additionally, we investigated the therapeutic potential of combining TG6002 with standard chemotherapeutic agents, including gemcitabine and components of the FOLFIRI regimen (irinotecan and oxaliplatin). In vitro, TG6002 demonstrated potent cytotoxicity against PDAC cells, which was further enhanced by the addition of 5-FC. Using a three-dimensional spheroid model, we confirmed TG6002’s ability to infect, replicate, and induce oncolysis. Furthermore, TG6002 replication was observed in surgically resected tumor tissues. Systemic administration of TG6002 showed significant antitumor activity in both subcutaneous and orthotopic PDAC models, with efficacy markedly improved by 5-FC administration. While TG6002 replication was inhibited by gemcitabine in vitro, TG6002 synergistically enhanced the cytotoxic effects of oxaliplatin and SN-38 (the active metabolite of irinotecan), primarily through increased apoptosis. In a xenograft model, systemic delivery of TG6002 with 5-FC, combined with either oxaliplatin or irinotecan, resulted in superior antitumor effects compared to monotherapy. In summary, our findings suggest that the systemic administration of TG6002 with 5-FC, in combination with irinotecan and oxaliplatin, represents a promising therapeutic strategy for PDAC patients.